Collocations and Grammatical Patterns in a Multilingual Online Term Bank - Taljard, Elsabé (Lexikos, 2015)
This article considers the importance of including various types of collocations in a terminological database, with the aim of making this information available to the user via the user interface. We refer specifically to the inclusion of empirical and phraseological collocations, and information on grammatical patterning. Attention is also given to provision of information on semantic prosody and semantic preferences — aspects which have been rather neglected in South African terminological databanks and language for special purposes (LSP) dictionaries. Various strategies for the effective semi-automatic extraction of collocational data from specialized corpora are explored. Possibilities regarding access to and presentation of collocational information to the user are briefly considered. It is argued that users should have direct access to collocational information, and that collocations should not only be accessible via the lemmatic address of the term appearing as part of the collocation. The research is done within the context of the establishment of an Open Access Resource Term Bank, which is developed as a pedagogical tool to support students whose language of learning and teaching is not the L1.